PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Audra Alessandra Wiennata; Wahyu Hidayat (Universitas Diponegoro, 2019)
In this era of globalization, the activity and mobility of the community has become increasingly rapid, hence the means of transportation is a part that is very much needed by the community in daily life. This opportunity causes competition among companies engaged in transportation services to attract consumers and retain consumers with the marketing strategies that they implement. One of the transportation services companies in Indonesia is PT Kereta Api Indonesia and one of the fleets owned is the Kaligung Train The purpose of this study was to determine the effect of Service Quality (X), on Customer Loyalty (Y) through customer Satisfaction (Z) (study on passengers of PT KAI DAOP IV Semarang Kaligung Train). This type of research is explanatory research. The number of samples taken was 100 respondents, who were passengers of the Kaligung train. The sampling technique uses purposive technique and accidental sampling. In analyzing the data using validity, reliability, cross tabulation, correlation coefficient, determination coefficient, simple linear regression analysis and t test using SPSS 21.0 for Windows software